1994
DOI: 10.1099/00221287-140-6-1427
|View full text |Cite
|
Sign up to set email alerts
|

Activation and pathway of glucosylglycerol synthesis in the cyanobacterium Synechocystis sp. PCC 6803

Abstract: The biosynthetic pathway of glucosylglycerol (GG), the osmoprotective compound of Synechocystis sp. PCC 6803, was found to proceed from ADPglucose and glycerol 3-phosphate via glucosylglycerol phosphate in a two-step reaction. Using an in vitro assay it was shown that the GG-forming enzyme system required activation, which could be initiated in vivo by hypertonic salt concentrations and osmotic shock, or in vitro by NaCl addition at the stage of enzyme extraction or assay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
100
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(102 citation statements)
references
References 22 publications
2
100
0
Order By: Relevance
“…We have evidence that T. thermophilus only possesses the two-step pathway leading to the synthesis of MG (N. Empadinhas, L. Pinto, A. Enke, H. Santos and M. S. da Costa, unpublished results). This two-step pathway is similar to those described for the synthesis of osmolytes like trehalose (Giaever et al, 1988), glucosylglycerol (Hagemann and Erdmann, 1994) and galactosylglycerol (Yokoyama et al, 1987), as all proceed via a phosphorylated intermediate. The existence of a single pathway for the synthesis of MG ) at 50°C for 20 min.…”
Section: Genes and Enzymes For The Synthesis Of Compatible Solutes Frmentioning
confidence: 81%
“…We have evidence that T. thermophilus only possesses the two-step pathway leading to the synthesis of MG (N. Empadinhas, L. Pinto, A. Enke, H. Santos and M. S. da Costa, unpublished results). This two-step pathway is similar to those described for the synthesis of osmolytes like trehalose (Giaever et al, 1988), glucosylglycerol (Hagemann and Erdmann, 1994) and galactosylglycerol (Yokoyama et al, 1987), as all proceed via a phosphorylated intermediate. The existence of a single pathway for the synthesis of MG ) at 50°C for 20 min.…”
Section: Genes and Enzymes For The Synthesis Of Compatible Solutes Frmentioning
confidence: 81%
“…A search of the P. horikoshii genome revealed an ORF (PH1879) that had 29% sequence similarity with the R. marinus MG synthase. However, the recombinant gene product had no measurable activity for the synthesis of MG. 2 The pathway for the synthesis of MG in P. horikoshii appears to be similar to those described for the synthesis of osmolytes like trehalose (32), glucosylglycerol (33), and galactosylglycerol (34), insofar as all proceed via two-step pathways involving a phosphorylated intermediate. The existence of a single pathway for the synthesis of MG in P. horikoshii instead of the branched pathway of R. marinus probably imposes a lower flexibility on the regulation of MG synthesis in response to osmotic and/or thermal stress.…”
Section: Pathway For Synthesis Of Mannosylglycerate In P Horikoshii mentioning
confidence: 96%
“…This salt dependence is actually a feature common to the biosynthetic pathways of other osmolytes such as, trehalose, glucosylglycerol, and galactosylglycerol, whose synthesis also occurs by two-step reactions, involving the concerted action of synthases and phosphatases (16,18,38). For instance, the synthesis of glucosylglycerol involves the condensation of ADP glucose and glycerol 3-phosphate to produce glucosylglycerol phosphate, which is subsequently dephosphorylated to yield glucosylglycerol (16). The enzymes involved in these biosynthetic pathways have not been purified or thoroughly characterized, but it has been shown that enzyme activities in crude extracts are strongly activated by potassium and sodium salts (16 -18, 38).…”
Section: Discussionmentioning
confidence: 99%
“…glycerate-By analogy with the known biosynthetic pathways of other sugar derivatives, such as glucosylglycerol (16) and trehalose (38), the terminal reaction in the synthesis of MG should involve a sugar nucleotide as donor of the glycosyl moiety, and a phosphorylated acceptor (3-P-glycerate). From an array of experiments with GDP mannose, UDP mannose, and ADP mannose as donors, and D-3-P-glycerate as acceptor, we were unable to detect the formation of MG in cell extracts prepared from R. marinus grown in medium containing 4% NaCl.…”
Section: Enzymatic Activities Involved In the Synthesis Of Mannosyl-mentioning
confidence: 99%
See 1 more Smart Citation